TEC variations and ionospheric disturbances during the magnetic storm in March 2015 observed from continuous GPS data in the Southeast Asia region - Minh*, Le Huy; Lan, Tran Thi; Fleury, R.; Amory Mazaudier, C.; Thanh, Le Truong; Thang, Nguyen Chien; Thanh, Nguyen Ha (Vietnam Journal of Earth Sciences, 2016)
The paper presents a method for computing the ionospheric total electron content (TEC) using the combination of the phase and code measurements at the frequencies f1 and f2 of the global positioning system, and applies it to study the TEC variations and disturbances during the magnetic storm in March 2015 using GPS continuous data in the Southeast Asia region. The computation results show that the TEC values calculated by using the combination of phase and code measurements are less dispersed than the ones by using only the pseudo ranges. The magnetic storm whose the main phase was on the 17th March 2015, with the minimum value of the SYM/H index of -223 nT is the biggest during the 24th solar cycle. In the main phase, the crests of the equatorial ionization anomaly (EIA) expanded poleward with large increases of TEC amplitudes, that provides evidence of the penetration of the magnetospheric eastward electric field into the ionosphere and of the enhancement of the plasma fountain effect associated with the upward plasma drifts. In the first day of the recovery phase, due to the effect of the ionospheric disturbance dynamo, the amplitude of northern crest decreased an amount of about 25% with respect to an undisturbed day, and this crest moved equatorward a distance of about 11o, meanwhile the southern crest disappeared completely. In the main phase the ionospheric disturbances (scintillations) developed weakly, meanwhile in the first day of the recovery phase, they were inhibited nearly completely. During the storm time, in some days with low magnetic activity (Ap< 50 nT), the ionospheric disturbances in the local night-time were quite strong. The strong disturbance regions with ROTI > 0.5 concentrated near the crests of the EIA. The latitudinal-temporal TEC disturbance maps in these nights have been established. The morphology of these maps shows that the TEC disturbances are due to the medium-scale travelling ionospheric disturbances (MSTID) generated by acoustic-gravity waves in the northern crest region of the EIA after sunset moving equatorward with the velocity of about 210 m/s. References Abadi P., S. Saito, and W. Srigutomo, 2014. Low-latitude scintillation occurrences around the equatorial anomaly crest over Indonesia, Ann. Geophys., 32, 7-17. Afraimovich E. L., 2008. First GPS-TEC evidence for the wave structure excited by the solar terminator, Earth, Planets and Space, 60, 895-900. Afraimovich E. L., E. I. Astafyeva, V. V. Demyanov, I. K. Edemskiy, N. S. Gavrillyuk, A. B. Ishin, E. A. Kosogorov, L. A. Leonovich, O. S. Lesyuta, K. S. Palamartchouk, N. P. Perevalova, A. S. Polyakova, G. Y. Smolkov, S. V. Voeykov, Y. V. Yasyukevich and I. V. Zhivetiev, 2013. A review of GPS/GLONASS studies of the ionospheric response to natural and anthropogenic processes and phenomena, J. Space Weather Space Clim., 3, A27, DOI:10.1051/swsc/2013049. Afraimovich E. L., I. K. Edemskiy, S. V. Voeykov, Yu. V. Yasyukevich and I. V. Zhivetiev, 2009. The first GPS-TEC imaging of the space structure of MS wave packets excited by the solar terminator, Ann. Geophys., 27, 1521-1525. Appleton E., 1946. Two anomalies in the ionosphere, Nature, 157, 691. Blanc M., A. Richmond, 1980. The ionospheric disturbance dynamo, J. Geophys. Res., 85, 1669-1686. Borries C., N. Jakowski and V. Wilken, 2009. Storm induced large scale TIDs observed in GPS derived TEC, Ann. Geophys., 27, 1605-1612. Budden K. G., 1985. The propagation of radio waves, Cambridge University Press, New York, 669p. Carrano C. & K. Groves, 2009. Ionospheric data processing and analysis. Workshop on Satellite Navigation Science and Technology for Africa, The Abdus Salam ICTP, Trieste, Italy. Davis M. J., 1971. On polar substorms as the source of large-scale traveling ionospheric disturbances, J. Geophys. Res., 76, 4525. Davies K. and J. E. Jones, 1971. Three-dimensional observations of traveling ionospheric disturbances, J. Atmos. Terr. Phys., 33, 39. Fejer B. G. and J. T. Emmert, 2003. Low‐latitude ionospheric disturbance electric field effects during the recovery phase of the 19-21 October 1998 magnetic storm. J. Geophys. Res., 108. doi: 10.1029/2003JA010190. Fejer B. G., C. A. Gonzales, D. T. Farley, M. C. Kelley and R. F. Woodman, 1979. Equatorial electric field during magnetically disturbed conditions: 1. the effect of interplanetary magnetic field, J. Geophys. Res., 84, 5797. Fejer B. G. & L. Scherliess, 1995. Time dependent response of equatorial ionospheric electric fields to magnetospheric disturbances, Geophys. Res. Lett., 22, 851-854. Fejer B. G., R. W. Spiro, R. A. Wolf and J. C. Foster, 1990. Latitudinal variation of perturbation electric fields during magnetically disturbed periods: 1986 SUNDIAL observations and model results, Ann. Geophys., 8, 441-454. Foster J. C. & F. J. Rich, 1998. Prompt mid-latitude electric field effects during severe geomagnetic storms, J. Geophys. Res., 103, 26367-26372. Francis S. H., 1974. A theory of medium-scale traveling ionospheric disturbances, J. Geophys. Res., 79, 34, 5245-5260. Georges T. M., 1968. HF Doppler studies of traveling ionospheric disturbances, J. Atmos. Terr. Phys., 30, 735. Gonzales C. A., M. C. Kelley, B. G. Fejer, J. F. Vickrey and R. F. Woodman, 1979. Equatorial electric fields during magnetically disturbed conditions: 2. Implications of simultaneous auroral and equatorial measurements, J. Geophys. Res., 84, 5803. Hines C. O., 1960. Internal atmospheric gravity waves at ionospheric heights, Can. J. Phys., 38, 1441. Jaggi R. K. and R. A. Wolf, 1973. Self-consistent calculation of the motion of a sheet of ions in the magnetosphere, J. Geophys. Res., 78, 2852-2866. Kelley M. C., B. G. Fejer and C. A. Gonzales, 1979. An explanation for anomalous equatorial ionospheric electric fields associated with a northward turning of the interplanetary magnetic field, Geophys. Res. Lett., 6, 301-304. Kelley M. C., J. J. Makela, J. L. Chau, and M. J. Nicolls, 2003. Penetration of the solar wind electric field into the magnetosphere/ionosphere system, Geophys. Res. Lett., 30(4), 1158, doi:10.1029/2002GL016321. J. Klobuchar, 1986. Design and characteristics of the GPS ionospheric time-delay algorithm for single frequency users, in: Proceedings of PLAN’86 -Position Location and Navigation Symposium, Las Vegas, Nevada, 280-286, 4-7, November. Kikuchi T., H. Lühr, K. Schlegel, H. Tachihara, M. Shinohara and T. I. Kitamura, 2000. Penetration of auroral electric fields to the equator during a substorm, J. Geophys. Res., 105, 23251-23261. Fuller-Rowell T. M., G. H. Millward, A. D. Richmond and M. V. Codrescu, 2002. Storm-time changes in the upper atmosphere at low latitudes, J. Atmos. Sol. Terr. Phys., 64, 1383. Tran Thi Lan, Le Huy Minh, 2011. The temporal variations of the total electron content (TEC) and the ionospheric scintillation according to the continuous GPS data in Vietnam, Journal of Sciences of the Earth, 33(4), 681-689. Tran Thi Lan, Le Huy Minh, R. Fleury, Tran Viet Phuong, Nguyen Ha Thanh, 2015. The occurrence characteristics of the ionospheric scintillation in Vietnam in the period 2009-2012, Journal of Sciences of the Earth, 37(3), 264-274 ( in Vietnamese). Le Huy Minh, C. Amory-Mazaudier, R. Fleury, A. Bourdillon, P. Lassudrie-Duchesne, Tran Thi Lan, Nguyen Chien Thang, Nguyen Ha Thanh, P. Vila, 2014. Time variations of the total electron content in the Southeast Asian equatorial ionization anomaly for the period 2006-2011, Advances in Space Research, 54, 355-368. Lin C. H., A. D. Richmond, J. Y. Liu, H. C. Yeh, L. J. Paxton, G. Lu, H. F. Tsai, S. -Y. Su, 2005. Large-scale variations of the low-latitude ionosphere during the October-November 2003 superstorm: Observational results, J. Geophys. Res., 110, A09S28, doi:10.1029/2004JA010900. Liu J. Y., H. F. Tsai and T. K. Jung, 1996. Total electron content obtained by using the global positioning system, Terr. Atmos. Oceanic Sci., 7, 107-117. Ma G. and T. Maruyama, 2006. A super bubble detected by dense GPS network at east Asian longitudes, Geophys., Res. Lett., 33, L21103, doi:10.1029/2003JA009931. Le Huy Minh, A. Bourdillon, P. L. Duschesne, R. Fleury, Nguyen Chien Thang, Tran Thi Lan, Ngo Van Quan, Le Truong Thanh, Tran Ngoc Nam, Hoang Thai Lan, 2006. The determination of the ionospheric total electron content in Vietnam from the data of GPS stations, Journal of Geology, A(296), 54-62. Munro G. H., 1958: Travelling ionospheric disturbances in the F region, Aust. J. Phys., 11, 91. Nishida A., 1968. Coherence of geomagnetic DP 2 fluctuations with interplanetary magnetic variations, J. Geophys. Res., 73(17), 5549. Peymirat C. and D. Fontaine, 1994. Numerical simulation of magnetospheric convection including the effect of field-aligned currents and electron precipitation, J. Geophys. Res., 99, 11155-11176. Pi X., A. J. Mannucci, U. J. Lindqwister and C. M. Ho, 1997. Monitoring of global ionospheric irregularities using the worldwide GPS network, Geophysical Research Letters, 24(18), 2283-2286. Richmond A. D., C. Peymirat, and R. G. Roble, 2003. Long-lasting disturbances in the equatorial ionospheric electric field simulated with a coupled magnetosphere-ionosphere-thermosphere model, J. Geophys. Res., 108(A3), 1118, doi:10.1029/2002JA009758. Spiro R. W., R. A. Wolf and B. G. Fejer, 1988. Penetration of high-latitude-electric-field effects to low latitudes during SUNDIAL 1984, Ann. Geophys., 6, 39-50. Saito A., S. Fukao and S. Miyazaki, 1998: High resolution mapping of TEC perturbations with the GSI GPS network over Japan, Geophys. Res. Lett., 25, 3079-3082. Sastri J. H., 1988. Equatorial electric fields of ionospheric disturbance dynamo origin, Ann. Geophys., 6(6), 635-642. Shimeis A., C. Borries, C. Amory-Mazaudier, R. Fleury, A. M. Mahrous, A. F. Hassan, S. Nawar, 2015. TEC variations along an East Euro-African chain during 5th April 2010 geomagnetic storm, Advances in Space Research, 55, 2239-2247. Shiokawa K., Y. Otsuka, M. K. Ejiri, Y. Sahai, T. Kadota, C. Ihara, T. Ogawa, K. Igarashi, S. Miyazaki and A. Saito, 2002. Imaging observations of the equatorward limit of midlatitude traveling ionospheric disturbances, Earth, Planets and Space, 54, 57-62. Spogli L., L. Alfonsi, G. De Franceschi, V. Romano, M. H. O. Aquino, A. Dodson, 2009. Climatology of GPS ionospheric scintillations over high and mid-latitude European regions, Ann. Geophys., 27, 3429-3437. Van Dierendonck A. J., J. Klobuchar, Quyen Hua, 1993. Ionospheric scintillation monitoring using commercial single frequency C/A code receivers, Proceedings of ION GPS-93. Vasyliunas V. M., 1970. Mathematical models of magnetospheric convection and its coupling to the ionosphere, in Particles and Fields in the Magnetosphere, edited by McCormac, 60-71, Springer, New York. Vasyliunas V. M., 1972. The interrelationship of magnetospheric processes, in Earth’s Magnetospheric Processes, edited by McCormac, 29-38, Springer, New York. Tsugawa T., Y. Otsuka, A. J. Coster and A. Saito, 2007. Medium-scale traveling ionospheric disturbances detected with dense and wide TEC maps over North America, Geophys. Res. Lett., 34, L22101, doi:10.1029/2007GL031663. Zhao B., W. Wan, L. Liu, Z. Ren, 2009. Characteristics of the ionospheric total electron content of the equatorial ionization anomaly in the Asian-Australian region during 1996-2004, Ann. Geophys., 27, 3861-3873.